Perancangan Aplikasi E-Rekrutmen dan Penempatan Karyawan Menggunakan Metode PSI pada PT. Mutiara Inti Persada - Utomo, Tedi; Ommi Alfina (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
PT. Mutiara Inti Persada is a company operating in the field of labor distribution services with the vision of providing and managing human resources professionally. However, employee recruitment and placement processes that are still carried out manually are often inefficient, lack objectivity, and face challenges in matching applicant profiles with the needs of partner companies. To overcome this problem, this research aims to design a web-based e-recruitment and employee placement application using the Preference Selection Index (PSI) method. The PSI method is applied to provide an objective assessment of applicants based on predetermined criteria, such as work experience, education, and skills. The system developed is also equipped with an employee placement feature designed to optimally match applicant profiles with the needs of partner companies. This research uses data collection methods through observation, interviews, and documentation to understand company needs, as well as a system development method using the Waterfall model. The research results show that the designed application is able to increase the efficiency of the recruitment process, reduce bias in applicant assessment, and ensure more appropriate employee placement.